Quality assurance in higher education: Trends and insights from a systematic literature review - Pramono, Suwito Eko; Widiyanto, Widiyanto (Edelweiss Applied Science and Technology, 2024)
Quality assurance in higher education is vital for ensuring institutional accountability, improving educational standards, and meeting stakeholder expectations. However, few studies offer clear directions for future research, highlighting the need for further exploration. To address this, this study uses a Systematic Literature Review (SLR) approach to map key research topics in quality assurance. A total of 2,578 Scopus-indexed articles published between 2013 and 2023 were analyzed, employing keyword co-occurrence mapping to identify thematic clusters. The data analysis was conducted using VOSviewer to uncover trends and advancements in the field. The results reveal four distinct clusters: The red cluster focuses on institutional and policy frameworks, highlighting the role of teaching, policy, and standards. The green cluster emphasizes student perceptions, satisfaction, and service quality, reflecting the growing importance of the student experience. The blue cluster examines accreditation processes, emphasizing their role in maintaining academic standards and ensuring compliance. The yellow cluster explores leadership and engagement, focusing on the relationship between school leadership, stakeholder involvement, and quality assurance practices. These findings offer a strong foundation for advancing both scholarly discourse and practical applications in quality assurance and provide valuable insights to guide future research in addressing emerging challenges in higher education.